2006
DOI: 10.1111/j.1365-294x.2006.03120.x
|View full text |Cite
|
Sign up to set email alerts
|

Absence of population structure of turbot (Psetta maxima) in the Baltic Sea

Abstract: We found low, albeit significant, genetic differentiation among turbot (Psetta maxima) in the Baltic Sea but in contrast to earlier findings we found no evidence of isolation by distance. In fact temporal variation among years in one locality exceeded spatial variation among localities. This is an unexpected result since adult turbot are sedentary and eggs are demersal at the salinities occurring in the Baltic. Our findings are most likely explained by the fact that we sampled fish that were born after/during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 84 publications
(86 reference statements)
4
49
0
Order By: Relevance
“…Very low genetic differentiation between samples was observed within the Atlantic region, supporting previous findings (Bouza et al., 2002; Coughlan et al., 1998; Florin & Höglund, 2007; Nielsen et al., 2004; Vandamme et al., 2014; Vilas et al., 2015), which indicates relatively high levels of gene flow. This is the case notwithstanding the presence of different well‐known current fronts inside the large marine ecosystems (LME) surveyed in this study, such as the Iberian Coastal, Irish and Biscay Shelf, and North Sea (Belkin & Cornillon, 2007; Belkin, Cornillon, & Sherman, 2009; Vandamme et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Very low genetic differentiation between samples was observed within the Atlantic region, supporting previous findings (Bouza et al., 2002; Coughlan et al., 1998; Florin & Höglund, 2007; Nielsen et al., 2004; Vandamme et al., 2014; Vilas et al., 2015), which indicates relatively high levels of gene flow. This is the case notwithstanding the presence of different well‐known current fronts inside the large marine ecosystems (LME) surveyed in this study, such as the Iberian Coastal, Irish and Biscay Shelf, and North Sea (Belkin & Cornillon, 2007; Belkin, Cornillon, & Sherman, 2009; Vandamme et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Differentiation due to selection (and genetic drift) may be favored by limited gene flow related to differences in salinity tolerance. It is known that Atlantic turbot eggs do not survive at the lower salinities of the Baltic Sea (Florin & Höglund, 2007), and, in addition, because turbot eggs are not buoyant at salinities below 20 PSU, eggs from the Baltic are demersal rather than pelagic (Nissling et al., 2006). Three of the five markers that were statistically significant in the ATL‐BAS comparison (1916_69 at LG9, 6850_51 and 7550_55 at LG2) were also significant in the comparison between ATL and BLS, strongly supporting that their divergence might be related to adaptation to differences in salinity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…the local turbot populations were studied using a wide range of morphological parameters, biochemical (3,7,18) and molecular markers (2,11,16,20). Several recent studies of natural turbot populations demonstrated a weak genetic structure among the populations from the northeast Atlantic and the low but significant genetic differentiation of turbot from the Baltic Sea (5,12,20). taken together the results from these studies suggest that turbot populations are related to high gene flow rate combined with low level of adaptive polymorphisms and genetic differentiation for some coastal areas.…”
Section: Introductionmentioning
confidence: 99%